Sepak Takraw Sports Development Management in Improving Soft Skills and Student Achievement in Educational Units - Pagayang, Rais; Badaru, Benny; Wahyuddin, Wahyuddin; Hudain, Muh. Adnan; Suwardi, Suwardi (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This article discusses the management of sepak takraw development as an effective means of improving soft skills and student achievement in educational institutions in North Toraja Regency. This study uses a descriptive qualitative approach with the aim of analyzing and describing in depth how the planning, organizing, implementing, and evaluating of sepak takraw development programs are managed to achieve these two objectives. Data collection was conducted through in-depth interviews with school principals, physical education teachers, coaches, and student representatives; participant observation of training sessions and competitions; and document analysis related to curriculum development programs and extracurricular activities. The results show that effective sepak takraw development management focuses not only on technical training for achieving sporting achievements but also integrates values ​​such as teamwork, discipline, leadership, and mental resilience into each training session. This integration has been shown to contribute significantly to improving students' soft skills, as measured by their interactions within the school and community. Furthermore, a well-managed program results in consistent improvements in sepak takraw achievement at the regional and national levels. In conclusion, sepak takraw development in North Toraja serves a dual function as an athletic development program and character building. Ongoing support from schools and local governments is needed to maintain this effective management model.